Built Environment and Users’ Behavior in Co-sharing Spaces: A Comparative Study of Traditional and Modern Real Estate Development in the Bangkok Metropolitan Region - Rattanaprichavej, Niti; Teeramungcalanon, Monthinee; Hogu, Kang (วารสารสถาปัตยกรรม การออกแบบและการก่อสร้าง, 2024)
The goal of this comparative study is to provide real estate developers, urban planners, and architects with a deeper understanding of the development and management of the built environment and users’ behaviour. This understanding can serve as an alternative investment strategy for the changing demands of the new target market. The main objectives of this research are 1) to study the behaviour of tenants and visitors in the environment of modern types of real estate development of the co-sharing spaces consisting of co-working space, serviced offices, and hostels and 2) to compare the modern types with traditional types of real estate consisting of home-based work/ café, traditional offices, and hotels. An in-depth structured interview of 19 samples was conducted as the primary approach to collecting information based on real estate in the Bangkok Metropolitan Region (BMR), Thailand. The result of this study reveals that the built environments of modern real estate types differ significantly from traditional types, particularly in terms of design objectives (functional, aesthetic, and symbolic). This difference also influences users’ physical determinism, which affects overt behaviour comprising personal space, territoriality, and privacy. However, this decline in overt behaviour does not imply a disadvantage in developing modern types of real estate projects. On the contrary, due to the users’ underlying concerns, developers can adapt these development concepts to enhance project opportunities in particular dimensions of cost-saving, focus and convenience, and new experiences. Therefore, properly balancing design objectives (aesthetic, symbolic, and functional aspects) and overt behavior (personal space, territoriality, and privacy) is crucial to conveying the success of development purposes for the new generations.